2007
DOI: 10.1523/jneurosci.0321-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2Protects Neonatal Mouse Brain from Hypoxic Ischemic Injury

Abstract: Prostaglandin D 2 (PGD) is synthesized by hematopoietic PGD synthase (HPGDS) or lipocalin-type PGDS (L-PGDS), depending on the organ in which it is produced, and binds specifically to either DP 1 or DP 2 receptors. We investigated the role of PGD 2 in the pathogenesis of hypoxic-ischemic encephalopathy (HIE) in neonatal mice at postnatal day 7. In wild-type mice, hypoxia-ischemia increased PGD 2 production in the brain up to 90-fold compared with the level in sham-operated brains at 10 min after cessation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 60 publications
4
64
0
Order By: Relevance
“…PGD was shown previously to have neuroprotective effects in a neonatal hypoxia-ischemia model (16). Consistent with the hypothesis that the protective effect of HCA 2 receptor-mediated neuroprotection is mediated via PGD 2 , Rahman and colleagues found that PGD 2 levels are elevated in both plasma and brain after nicotinic acid treatment.…”
Section: The New Ketone Alphabet Soup: Bhb Hca and Hdacsupporting
confidence: 52%
“…PGD was shown previously to have neuroprotective effects in a neonatal hypoxia-ischemia model (16). Consistent with the hypothesis that the protective effect of HCA 2 receptor-mediated neuroprotection is mediated via PGD 2 , Rahman and colleagues found that PGD 2 levels are elevated in both plasma and brain after nicotinic acid treatment.…”
Section: The New Ketone Alphabet Soup: Bhb Hca and Hdacsupporting
confidence: 52%
“…Previous work has shown that PGD 2 helps to resolve inflammation 42 . In addition, it has neuroprotective effects 22,43 . PGD 2 has a short half-life in tissue and is spontaneously converted into the cyclopentenone 15-deoxy-D 12,14 -prostaglandin J 2 (15d-PGJ 2 ), which inhibits the IkB kinase (IKK), the main activator of the transcription factor NF-kB and a key player in ischemic brain damage 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, PGD 2 is responsible for the flushing response induced by nicotinic acid. In the brain, however, PGD 2 exerts neuroprotective effects 22 . Therefore, we investigated whether PGD 2 production mediates the neuroprotective effect of HCA 2 activation.…”
Section: Hca 2 Mediates the Neuroprotective Effect Of Ketogenic Dietmentioning
confidence: 99%
“…Taken together, these data demonstrate novel and paradoxical protective effects of additional prostaglandin receptors in organotypic models of glutamate toxicity. The effects of prostaglandin receptors in organotypic models of excitotoxicity so far predicts their roles in vivo in models of cerebral ischemia where glutamate toxicity is an early and acute event [15,16,21].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the EP2 receptor mediates a significant protective function in models of focal ischemia [15,16]. PGD 2 , signaling via its DP1 receptor similarly rescues CA1 and CA3 neurons in organotypic hippocampal slices treated with NMDA [14] and in vivo in a model of postnatal hypoxia-ischemia [21]. Mechanistically, EP2 and DP1 neuroprotection are dependent on intact cAMP signaling, whereas EP3 neuroprotection is associated with increased AKT phosphorylation [3,16].…”
Section: Introductionmentioning
confidence: 99%